The Effect of Combining Smoothies on Blood Pressure in Hypertensive Patients - Diana Rhismawati Djupri; Adinda Prameswari Puspita Wahyuningrum; Nana Andriana; Eva Trisna; Rusmala Dewi; Aat Yatnikasari (PT.Mantaya Idea Batara, 2026)
Background: Hypertension remains a significant cardiovascular health issue, especially in rural communities. Dietary interventions rich in potassium, antioxidants, and probiotics may offer supportive, non- pharmacological options in complementary nursing care. This study evaluated blood pressure changes after consuming a smoothie containing bananas, strawberries, yogurt, and honey in patients with hypertension Methods: Using a quasi-experimental, single-group pretest–posttest design, 18 participants were recruited through consecutive sampling. Each participant consumed 250 mL of the standardized smoothie daily for seven days. Blood pressure was measured before and after the intervention with a calibrated digital sphygmomanometer, following a standardized resting protocol. The Shapiro–Wilk test assessed normality of paired differences, and paired- samples t-tests compared pre- and post-intervention blood pressure Result: included 95% confidence intervals and Cohen’s d effect sizes. Mean systolic blood pressure decreased by 14.05 mmHg, from 155.72 ± 10.45 mmHg to 141.67 ± 9.82 mmHg (p < 0.001; 95% CI: 9.52–18.58; Cohen’s d = 1.38). Mean diastolic blood pressure decreased by 6.44 mmHg, from 99.72 ± 7.65 mmHg to 93.28 ± 6.41 mmHg (p = 0.002; 95% CI: 2.81–10.07; Cohen’s d = 0.91). These results suggest that seven days of smoothie consumption was associated with significant reductions in both systolic and diastolic blood pressure Conclusion: However, due to the single-group design and small sample size, randomized controlled trials are needed to confirm causal effectiveness and address potential confounding factors.